2019
DOI: 10.1001/jama.2019.2341
|View full text |Cite|
|
Sign up to set email alerts
|

Intramyocardial Injection of Mesenchymal Precursor Cells and Successful Temporary Weaning From Left Ventricular Assist Device Support in Patients With Advanced Heart Failure

Abstract: IMPORTANCE Left ventricular assist device (LVAD) therapy improves myocardial function, but few patients recover sufficiently for explant, which has focused attention on stem cells to augment cardiac recovery. OBJECTIVE To assess efficacy and adverse effects of intramyocardial injections of mesenchymal precursor cells (MPCs) during LVAD implant. DESIGN, SETTING, AND PARTICIPANTS A randomized phase 2 clinical trial involving patients with advanced heart failure, undergoing LVAD implant, at 19 North American cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 17 publications
0
62
0
Order By: Relevance
“…They have great advantages of easy accessibility, easy manipulation, and low HLA typing restriction, com-bined with their promising features of self-renewal and multipotency, making them the most commonly used adult stem cells in regenerative medicine. MSCs have been widely used in clinical trials for the treatment of diseases including hematological diseases, graft-versushost diseases, diabetes, end-stage diseases in the liver, kidney, and lung, autoimmune diseases, and various neurological diseases [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…They have great advantages of easy accessibility, easy manipulation, and low HLA typing restriction, com-bined with their promising features of self-renewal and multipotency, making them the most commonly used adult stem cells in regenerative medicine. MSCs have been widely used in clinical trials for the treatment of diseases including hematological diseases, graft-versushost diseases, diabetes, end-stage diseases in the liver, kidney, and lung, autoimmune diseases, and various neurological diseases [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, a suspected complication was mucosal oozing at injection sites when used in patients with heart failure, especially those undergoing ventricular assist device insertion where this complication is more common. However, it was found that the incidence of this complication was not increased in the limited cases performed, though it should be noted this study used a cell-based therapy (Yau et al, 2019). Given IMI involves injecting a foreign substance directly into the myocardium, a theoretical risk could be if the gel ruptures through the endocardium and embolizes, causing neurological and systemic complications.…”
Section: Complicationsmentioning
confidence: 87%
“…MSCs including BMSCs are capable of differentiating into cells of multiple cell lineages, exhibit potent paracrine function, and thus are considered an ideal source for cell therapy in regenerative medicine because of their easy preparation and low immunogenicity without ethical concerns. However, the outcomes of clinical studies with MSCs have been inconsistent and inconclusive for unknown reasons (Majka, Sulkowski, Badyra, & Musialek, 2017; Yau et al, 2019). Age could reduce overall cell yield of all MSC populations, and age of the donors appears to be an important factor for the function and therapeutic potency of BMSCs (Beane et al, 2014; Charif et al, 2017; Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%